Legal Implications of Data Breach Cases in Indonesia: Challenges And Solutions in The Era of Personal Data Protection - Lala, Andi; Abdullah, Abdullah (Indonesian Cyber Law Review, 2024)
In the digital era, cases of Data leaks in Indonesia continue to increase, causing various implications for the law on personal data protection. Inadequate regulation and a lack of law enforcement lead to uncertainty and financial loss for individuals and organizations. Therefore, an effective solution is needed​ to overcome the challenges in the era of personal data protection. Study This aiming to analyze the implications of the law from case data leaks in Indonesia and offers solutions to face the challenges that arise along with the implementation of the Constitution on Personal Data Protection. This study employs a qualitative method with a case study approach. Data obtained through analysis of documents, laws, regulations, and studies of literature about data leaks in Indonesia. Additionally, interviews with expert lawyers and practitioners in the field of data security are conducted to gain a more in-depth understanding. Research results show that challenges in personal data protection in Indonesia include the uncertainty of the law, weak enforcement of regulations, and a lack of public awareness. Research This also provides recommendation policy For strengthen regulation and improve mechanism personal data protection in Indonesia.